Electrolyte/Structure-Dependent Cocktail Mediation Enabling High-Rate/Low-Plateau Metal Sulfide Anodes for Sodium Storage - Tang, Yongchao; Wei, Yue; Hollenkamp, Anthony F.; Musameh, Mustafa; Seeber, Aaron; Jin, Tao; Pan, Xin; Zhang, Han; Hou, Yanan; Zhao, Zongbin; Hao, Xiaojuan; Qiu, Jieshan; et al. (Nano-Micro Letters, 2021)
As promising anodes for sodium-ion batteries, metal sulfides ubiquitously suffer from low-rate and high-plateau issues, greatly hindering their application in full-cells. Herein, exemplifying carbon nanotubes (CNTs)-stringed metal sulfides superstructure (CSC) assembled by nano-dispersed SnS2 and CoS2 phases, cocktail mediation effect similar to that of high-entropy materials is initially studied in ether-based electrolyte to solve the challenges. The high nano-dispersity of metal sulfides in CSC anode underlies the cocktail-like mediation effect, enabling the circumvention of intrinsic drawbacks of different metal sulfides. By utilizing ether-based electrolyte, the reversibility of metal sulfides is greatly improved, sustaining a long-life effectivity of cocktail-like mediation. As such, CSC effectively overcomes low-rate flaw of SnS2 and high-plateau demerit of CoS2, simultaneously realizes a high rate and a low plateau. In half-cells, CSC delivers an ultrahigh-rate capability of 327.6 mAh g−1anode at 20 A g−1, far outperforming those of monometallic sulfides (SnS2, CoS2) and their mixtures. Compared with CoS2 phase and SnS2/CoS2 mixture, CSC shows remarkably lowered average charge voltage up to ca. 0.62 V. As-assembled CSC//Na1.5VPO4.8F0.7 full-cell shows a good rate capability (0.05 1.0 A g−1, 120.3 mAh g−1electrode at 0.05 A g−1) and a high average discharge voltage up to 2.57 V, comparable to full-cells with alloy-type anodes. Kinetics analysis verifies that the cocktail-like mediation effect largely boosts the charge transfer and ionic diffusion in CSC, compared with single phase and mixed phases. Further mechanism study reveals that alternative and complementary electrochemical processes between nano-dispersed SnS2 and CoS2 phases are responsible for the lowered charge voltage of CSC. This electrolyte/structure-dependent cocktail-like mediation effect effectively enhances the practicability of metal sulfide anodes, which will boost the development of high-rate/-voltage sodium-ion full batteries. Highlights: 1 Nano-dispersed SnS2 and CoS2 phases endow CSC anode with electrolyte/structure-dependent cocktail mediation effect, showing superior rate capability and evidently lowered charge plateau compared with CoS2 and SnS2/CoS2 mixture. 2 Alternative electrochemical processes between nano-dispersed different metal sulfides and Na+ carriers effectively overcome intrinsic flaws of monometallic sulfide, responsible for the lowered charge plateau of CSC. 3 As-assembled CSC//Na1.5VPO4.8F0.7 full-cell shows high-rate capability, and high discharge plateau up to 2.57 V, which is comparable to that with alloy-type anodes.